LITERATURE STUDY: COST BEHAVIOR ANALYSIS - Vivi Usmayanti (TECHNOBIZ : International Journal of Business, 2022)
Currently there are many types of companies/businesses in Indonesia. Business people / business people are very interested in understanding the price structure. This study aims to explain the basic concepts in the evolution of conceivable cost behavior from theoretical and practical cost behavior. The writing of this article provides a complete picture of the concept of cost behavior studied based on the results of previous research. This research is a literature study with a descriptive research nature, using various written sources such as articles, books and documents relevant to this research. This literature review focuses on behavior-based cost sharing, which plays an important role in determining production costs for a business, including a company.Keywords: Behavioral Costs, Fixed Costs, Variable Costs, Semi-Variable Costs